Writing a Helpful Referee's Report - Martin, Brian (Journal of Scholarly Publishing, 2008)
Referees’ reports are often demoralizing to authors. It is possible to write a report that is supportive and helpful by following two rules: Say what is good about a piece of work, and say how it can be improved.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuMzkuMy4zMDE